Mental Health Promotion and Illness Prevention in Vulnerable Populations - Laranjeira, Carlos (2024)
Several cases of social and health inequity have occurred in recent centuries. Despite major innovations and significant changes in the general population’s quality of life, the most vulnerable populations continued to survive [1]. Vulnerability is a general concept that, in the context of health, means susceptibility to developing a certain health problem. Thus, vulnerable populations are those at greater risk of developing physical, psychological, or social health problems due to their marginalized socio-cultural status, their limited access to economic resources, or due to individual characteristics such as gender or age [2]. Vulnerability, as a human being’s ontological condition [3,4], can be aggravated by experiencing a transition, exposing the client to potential danger, a problematic or excessively long recovery, or an inadequate or delayed adaptation process [5,6].